La poesia dell'estasi - Canettieri, Paolo (Cognitive philology, 2010)
An essentially rationalistic approach of literary stories caused that the ecstatic confessions and, more generally, the poetry that sings the union with God were relegated in a corner together, moreover, with a multitude of other expressions of spirituality. However, it might furnish many tests to show that already in the thirteenth century the ecstasy became consciously sayable in poetry and that, since it was high poetry, it would be wrong not to include these tests as part of a wider European canon. Here, therefore, we focus attention on those forms of medieval lyricism, through which some authors, men and especially women, have tried to make the experience of mysticism poetic. Reflection, we believe, may be oriented in two methodological directions: the cognitive and the anthropological approach, that will search in the human universal the moments of affinity with the operation of the Western mystics: In this sense, anthropology, cognitive psychology and comparative European Literature may find a useful connection point to explain matters that would not make sense in a frame exclusively descriptive or taxonomic.